2003
DOI: 10.1038/sj.jhh.1001575
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure response to changes in sodium and potassium intake: a metaregression analysis of randomised trials

Abstract: The objective of the study was to assess the blood pressure response to changes in sodium and potassium intake and examine effect modification by age, gender, blood pressure, body weight and habitual sodium and potassium intake. Randomised trials of sodium reduction or potassium supplementation and blood pressure were identified through reference lists of systematic reviews and an additional MEDLINE search (January 1995-March 2001. A total of 40 sodium trials and 27 potassium trials in adults with a minimum d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
220
3
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 365 publications
(240 citation statements)
references
References 78 publications
8
220
3
5
Order By: Relevance
“…Our results are also similar to the findings of a 24-week randomised trial in 55-75-year-old untreated Dutch hypertensives in which the same salt replacement product was used (38) . The DASH 8-week feeding study, however, demonstrated a much greater BP reduction (213?2/26?1 mmHg) in the subgroup analyses for African-Americans with hypertension (13) .…”
Section: Discussionsupporting
confidence: 88%
“…Our results are also similar to the findings of a 24-week randomised trial in 55-75-year-old untreated Dutch hypertensives in which the same salt replacement product was used (38) . The DASH 8-week feeding study, however, demonstrated a much greater BP reduction (213?2/26?1 mmHg) in the subgroup analyses for African-Americans with hypertension (13) .…”
Section: Discussionsupporting
confidence: 88%
“…A meta-analysis of randomised trials indicated that a reduction in sodium and an increase in potassium consumption lowers blood pressure in normotensive and hypertensive individuals (68,69) .…”
Section: Effect Of the Mediterranean Diet On Hypertensionmentioning
confidence: 99%
“…Two recent meta-analyses 15,16 have revealed that an approximately 75 mmol a day (about 50%) reduction in the intake of sodium lowers blood pressure in both subjects with hypertension and normotensive individuals. In hypertensives, the fall in systolic blood pressure is about 5 mmHg and that in diastolic pressure, approximately 3 mmHg.…”
Section: Effect Of Sodium Reduction Alonementioning
confidence: 99%
“…An increase of potassium intake by approximately 1.8-1.9 g a day has proved to lower the blood pressure of hypertensive subjects so that the average fall in systolic blood pressure is approximately 4 mmHg and that in diastolic pressure, about 2.5 mmHg 16,17 This increase in potassium intake is about 25% of the amount provided by a 2100 kcal Natural Diet, and not sufficient to raise the potassium intake in USA to the currently recommended level of 4.7 g per day.…”
Section: Effect Of Increased Potassium Intake Alonementioning
confidence: 99%